Trading frequency and implied transaction costs of options: evidence from the Australian index option market - Abdullah, Mimi Hafizah; Li, Steven (2010)
This study examines the pricing performance of a few option pricing models in valuing call options on S&P/ASX 200 index with different transaction costs under various trading frequencies. The option pricing models of the original Leland model as well as its two variations are tested and contrasted with the Black-Scholes-Merton (BSM) model across moneyness and maturity. For the purpose of discussion, we focus on at-the-money call options as they are the most liquid options. Our empirical results reveal that at low transaction costs, the two variations of the original Leland model regardless of their trading frequencies appear to perform well in pricing at-the-money call options. Furthermore, the examination of the estimates of the implied transaction costs in S&P/ASX 200 index options reveals that as trading becomes more frequent (from quarterly to daily), the implied transaction costs decreases. Moreover, the longer the time to maturity, the larger the implied transaction costs.